2011
DOI: 10.15835/nsb325636
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Yield and Fiber Technological Properties of Cotton (Gossypium hirsutum L.)

Abstract: The aim of this study was to determine the variability in yield and fiber technological properties in advanced cotton lines developed through cotton breeding program of the Southeastern Anatolia Agricultural Research Institute (SAARI). The experiment was conducted in the SAARI's experimental field according to Augmented Design (AD) with six replications. In the study, 66 advanced cotton breeding lines and 3 control varieties ('Stoneville 468' , 'GW-Teks' , and 'Fantom') were used as plant materials. -1 for fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Various researchers reported that the growth of cultivars varied by arid and low land conditions and that irrigation and rainfall increased the seed yield at the stages of branching and seed formation; furthermore, yield and crop traits were shown to vary by cultivar, ecological conditions, and agronomic practices. The large number of genotypes allows observation of exiting genetic variation which could be used to develop hybridization programs among the genotypes for the development of new cultivars with high yield potential, high oil content, and different fatty acid compositions (Mary and Gopalan 2006;Karademir et al 2007). In the present study, safflower genotypes originated from different countries were evaluated for their adaptation ability in Isparta ecological condition to reveal suitable types for further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers reported that the growth of cultivars varied by arid and low land conditions and that irrigation and rainfall increased the seed yield at the stages of branching and seed formation; furthermore, yield and crop traits were shown to vary by cultivar, ecological conditions, and agronomic practices. The large number of genotypes allows observation of exiting genetic variation which could be used to develop hybridization programs among the genotypes for the development of new cultivars with high yield potential, high oil content, and different fatty acid compositions (Mary and Gopalan 2006;Karademir et al 2007). In the present study, safflower genotypes originated from different countries were evaluated for their adaptation ability in Isparta ecological condition to reveal suitable types for further studies.…”
Section: Introductionmentioning
confidence: 99%